Characterizing the Pregnancy Immune Phenotype: Results of the Viral Immunity and Pregnancy (VIP) Study - Kraus, Thomas A. (J Clin Immunol, 2011)
PURPOSE: The increased risk of morbidity and mortality from certain microbial infections and the demonstrated improvements in the clinical course of some autoimmune diseases support the existence of pregnancy-related alterations in immune status. Elucidating the changes in innate and adaptive immunity during gestation may improve pregnancy outcomes and facilitate the development of targeted therapies for autoimmune diseases. METHOD: The Viral Immunity and Pregnancy (VIP) study evaluated over 50 subjects longitudinally at three time points during pregnancy and at two time points post-delivery. Leukocyte enumeration was performed; functional responses of NK cells and CD4 T cells were analyzed, and soluble factors such as cytokines, defensins, and steroid hormones were measured in maternal blood. RESULTS: In comparison to the post-partum period, the latter part of pregnancy was characterized by significant increases in blood phagocytes and pDCs and decreases in the number and activity of NK and T cells. Alterations were found in antimicrobial proteins and serum cytokines. CONCLUSIONS: These data show that pregnancy is not a period of immunosuppression but an alteration in immune priorities characterized by a strengthening of innate immune barriers and a concomitant reduction in adaptive/inflammatory immunity in the later stages of pregnancy.